2015
DOI: 10.1038/srep08441
|View full text |Cite
|
Sign up to set email alerts
|

Driving a GaAs film to a large-gap topological insulator by tensile strain

Abstract: Search for materials with a large nontrivial band gap is quite crucial for the realization of the devices using quantum spin Hall (QSH) effects. From first-principles calculations combined with a tight-binding (TB) model, we demonstrate that a trivial GaAs film with atomic thickness can be driven to a topological insulator with a sizable band gap by tensile strain. The strain-induced band inversion is responsible for the electronic structure transition. The nontrivial band gap due to spin-orbital coupling (SOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 34 publications
0
54
1
Order By: Relevance
“…Starting from graphene [38], many kinds of QSH insulators have been predicted, including graphene with a sandwich structure [39,40], silicene (germanene/stanene) with RHF [41,42], stanene with a dumbbell structure [43][44][45], MoS 2 allotropes [46][47][48][49][50][51][52], and monolayers containing heavy metal atoms (Bi/Sb/Hf) [24,[53][54][55][56]. In the case of particular substrates [57], applying an external field [58], or using hydrogenation/functionalization [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78], the size of those nontrivial bulk gaps can be further increased. Currently, the largest nontrivial bulk gap is 1.08eV found in Bi 2 F 2 monolayer [59,60], which shows that chemical functionalization is a very powerful way to obtain a large nontrivial bulk gap.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from graphene [38], many kinds of QSH insulators have been predicted, including graphene with a sandwich structure [39,40], silicene (germanene/stanene) with RHF [41,42], stanene with a dumbbell structure [43][44][45], MoS 2 allotropes [46][47][48][49][50][51][52], and monolayers containing heavy metal atoms (Bi/Sb/Hf) [24,[53][54][55][56]. In the case of particular substrates [57], applying an external field [58], or using hydrogenation/functionalization [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78], the size of those nontrivial bulk gaps can be further increased. Currently, the largest nontrivial bulk gap is 1.08eV found in Bi 2 F 2 monolayer [59,60], which shows that chemical functionalization is a very powerful way to obtain a large nontrivial bulk gap.…”
Section: Introductionmentioning
confidence: 99%
“…Group V elements, including Bi [28,29], Sb [30] thin films are also found to be large-gap QSH insulators, when functionalized with hydrogen or halogen atoms. More recently, functionalized group III-V materials GaAs and GaBi have also reported to be large-gap QSH insulators [31,32]. These large-gap QSH insulators are essential for realizing many exotic phenomena and for fabricating new quantum devices that can operate at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, our recent work showed that tensile strain can serve as an effective means to drive a normal insulator to a QSH insulator 21 .…”
Section: Introductionmentioning
confidence: 99%